Pertumbuhan Tradisi Filsafat di Dunia Islam: Tafsir Historis - Rubiyanah Rubiyanah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The development of philosophy in Islam did not emerge from a vacuum. It is an accumulation of interactions from various civilizations triggered by the evolution of discourse within Islam. Theological issues certainly occupy a significant position in the religious discourse structure. However, it cannot be denied that political, cultural, and other social aspects also play a role in the continuity of discourse and philosophical tradition in Islam. Hence, theological controversies arising from hermeneutic differentiations of religious texts become inevitable. The following article discusses the intersections among diverse civilizations that contribute to the development of philosophy in Islam.